FAKTOR-FAKTOR YANG MEMPENGARUHI RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PERIODE 2013-2015 - Winda Zuliyanti, 14.05.62.0005; Indarti, MG. Kentris (Students Journal of Accounting and Banking, 2017)
This study examines the factors that affect stock returns in manufacturing companies food and beverage sector listed on the IDX period 2013-2015. This research is conducted at Indonesia Stock Exchange by using unit analysis of manufacturing company of food and beverage sector. Sampling method using purposive sampling, that is sample determination technique by using certain criteria. The relationship or influence between variables is explained by using multiple linier regression analysis method and hypothesis test (t test). The results showed that the variable Return On Equity (ROE) has a negative and significant effect on stock returns, variable Current Ratio (CR) has no significant effect on stock return, Debt to Equity Ratio (DER) variable has no significant effect on Stock returns and exchange rate variables have a negative and significant effect on stock returns.Keywords: ROE, CR, DER, EPS, Exchange Rate and Stock Return